Emotional reactions to concepts of racism and white privilege in non-Aboriginal professionals working in remote Aboriginal communities - Caitlin Prince (James Cook University, 2024)
Introduction: This research, conducted by a non-Aboriginal, White researcher, examines how health professionals working in remote Aboriginal communities engage with antiracism as instructed by national standards, whether strong emotions are elicited while reflecting on these concepts, and how these reactions impact on antiracist professional practice. Methods: Eleven non-Indigenous allied health professionals were interviewed in a semi-structured format. Interviews were transcribed, thematically analysed and compared to existing literature. Results and discussion: Every participant identified overwhelming emotions that they linked to reflecting on racism, White privilege and colonisation. Professionals reported grappling with denial, anger, guilt, shame, fear, anxiety and perfectionism, loss of belonging, disgust and care. They reported that these emotions caused overwhelm, exhaustion, tensions with colleagues and managers, and disengagement from antiracism efforts, and contributed to staff turmoil and turnover. Conclusion: Previously, these emotional reactions and their impact on antiracism have only been described in the context of universities and by antiracist activists. This research identifies for the first time that these reactions also occur in health services in Aboriginal communities. Wider research is needed to better understand how these reactions impact on health service delivery to Aboriginal communities, and to evaluate ways of supporting staff to constructively navigate these reactions and develop antiracist, decolonised professional practice.